Organisational structure as a driver of mergers and acquisitions in the European banking sector - Laura Lebastard (European Central Bank (ECB), 2022)
This paper studies the bilateral drivers of mergers and acquisitions (M&As) between European banks. Two findings document that banks use M&A as a device to leverage their expertise rather than to diversify. (i) Following the literature on matrimonial matching by using a binary logit model, the paper examines how the structure of acquiring banks in terms of geographical location (headquarters and subsidiaries) influences the choice of targeted banks for an M&A transaction. It finds that banks favour domestic expansion over international diversification. (ii) The paper investigates how the business model of acquiring banks determines their selection of targeted banks. Very often, banks tend to target counterparts with the same business model or, to a lesser extent, those with the same business model as one of their subsidiaries.
Keywords: G21; G34; L22; 330; Banks; mergers and acquisitions; internal organisation; domestic footprint; economies of scale